Fragile Land - Cramb, Auslan (Edinburgh University Press, 1999)
A mini-encyclopaedia of environmental facts and figures with case studies from leading scientists and academics, describing the environment as it exists today, and offering solutions to pressing problems from air pollution to the loss of plants and animals.